Combinatorial Semasiology: Selective Component of Lexical Meaning of Word - M. V. Vlavatskaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to a selective component, which is a part of the syntagmatic component of lexical meaning of a word and has its purpose - to elect and to restrict the combinability of words considering the subject and logical links in extralinguistic reality; to elect and restrict the combinability of words that express human feelings, and to waive the requirement of a certain functional style. It is shown that the selective component of meaning has an impact on a number of important semantic functions: firstly, it contributes to the differentiation of lexical-semantic variants of polysemantic words; secondly, it allows to identify variations and nuances of the same meaning, to combine them into a single meaning in case, if a word shows similar use; thirdly, it contributes to the reflection of the typical notions about the objects and phenomena that exist in reality. It is noted that the selective component has the meaning of a word specifying the rules of using it in the speech circuit, and outputs the meaning in syntagmatics; in addition, it may be determined by the denotation, connotation or stylistic affiliation of combined words. It is indicated that the study is conducted in the framework of combinatorial semasiology studying the ratio of the semantics of word and its compatibility.